2015
DOI: 10.1177/1078155215587541
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mental health literacy in patients with breast cancer

Abstract: Our results suggest that the mental health literacy of breast cancer patients was inadequate. Intervention and management strategies could be implemented to teach these patients about evidence-based treatments and professional help that are specific to mental disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 34 publications
2
40
1
Order By: Relevance
“…Regarding information other than that on treatment, patients strongly wished to obtain "information on how to communicate with healthcare professionals," further suggesting that patients may have felt there was a communication gap. In terms of health information, relationships between health literacy and physical/mental activity have been reported [19,20]. This health literacy refers to the ability of a patient to recognize the symptoms of physical and mental illness and be aware of both self-treatment and professional help available for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding information other than that on treatment, patients strongly wished to obtain "information on how to communicate with healthcare professionals," further suggesting that patients may have felt there was a communication gap. In terms of health information, relationships between health literacy and physical/mental activity have been reported [19,20]. This health literacy refers to the ability of a patient to recognize the symptoms of physical and mental illness and be aware of both self-treatment and professional help available for these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As Asians are generally influenced by culture and beliefs, it is important to ensure that the content of our programme suits the needs of Asian BCS. This is quite evident from findings of our other preliminary studies . For example, we learned that BCS utilize traditional Chinese medicine and meditation to improve their memory and related adverse effects.…”
Section: Discussionmentioning
confidence: 67%
“…Asian practitioners surveyed indicated that financial constraints, patients' lack of awareness, and unwillingness to discuss sensitive issues are significant patient‐related barriers. Another study evaluating mental health literacy in Asian BCS suggests that Asian patients significantly lack knowledge in identifying symptoms for cognitive disturbances, anxiety, and depression, which may prevent survivors from proactively seeking medical attention . In summary, the lack of holistic follow‐up care by practitioners, together with patient factors that deter patients from seeking professional help for survivorship concerns, result a major unmet needs in the current practice.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we did not compare attitudes with other modifiable individual variables like anticipated stigma or mental health literacy. These variables were also recently considered to influence psychological care utilisation of patients with cancer (Cheung et al, ; Cohen et al, ; Rose et al, ). Third, we exclusively assessed patients’ attitudes, although the attitudes of family members or primary caregivers probably influence help‐seeking.…”
Section: Discussionmentioning
confidence: 99%
“…These variables were also recently considered to influence psychological care utilisation of patients with cancer (Cheung et al, 2016;Cohen et al, 2018;Rose et al, 2018). Third, we exclusively assessed patients' attitudes, although the attitudes of family members or primary caregivers probably influence help-seeking.…”
Section: Study Limitationsmentioning
confidence: 99%